Campuhan: A New Music Creation | Campuhan: Sebuah Musik Kreasi Baru - Gede Made Rama Pratama; Saptono - (GHURNITA: Jurnal Seni Karawitan, 2021)
Mixed means mixed, which in this case is a mixture of human moods or emotions. Campuhan is an innovative musical work that tells the mood of someone who has bipolar mental disorder (drastic emotional changes), by implementing it into a new musical composition with the express media, Semara Pegulingan, Angklung Klentang, and Balaganjur as a form of three emotional bases, namely neutral (tranquility). or happiness), depressive (sadness or sadness), and manic (excited or ambitious). The structure of Campuhan's work is divided into three parts, the first part is a symbol of a neutral emotional state using the medium of saying Semara Pegulingan, the second part is a symbol of a depressive emotional state using the media of Angklung Klentang, and the third is a symbol of a manic emotional state. with the media said Balaganjur. The venue for the performance was in Banjar Antap Kaja Office, Antap Village, Kec. Selemadeg, Kab. Tabanan, precisely at the stylist's house. The supporting members of the work are thirteen personnel, including the stylist, from the Natya Praja Studio and the Kapiwara Studio.